High-valence cation-doped sulfide solid-state electrolyte and liquid-phase synthesis method and application thereof
Patent Information
- Application Number
- CN202611048704.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-07-15
AI Technical Summary
[0006]鉴于上述现有技术的不足,本发明的目的在于提供一种高价阳离子掺杂硫化物固态电解质及其液相合成方法与应用,旨在解决现有合成方法存在能耗高、成分均匀性差以及高价阳离子难以完全固溶的问题
[0006]鉴于上述现有技术的不足,本发明的目的在于提供一种高价阳离子掺杂硫化物固态电解质及其液相合成方法与应用,旨在解决现有合成方法存在能耗高、成分均匀性差以及高价阳离子难以完全固溶的问题。
Smart Images

Figure CN122540819B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of new energy battery technology, and in particular to a high-valence cation-doped sulfide solid electrolyte and its liquid-phase synthesis method and application. Background Technology
[0002] With the accelerated global energy structure transformation, sodium-ion batteries are considered a core candidate technology for next-generation large-scale energy storage systems due to their advantages such as abundant sodium resources, low cost, and even geographical distribution. Sulfide solid electrolytes, with their ultra-high room-temperature sodium-ion conductivity (up to 10⁻⁶), are particularly promising. -3 -10 -2 With its S / cm level, good mechanical ductility, and cold-pressing properties, it has become one of the most promising solid electrolyte materials in the field of all-solid-state sodium batteries.
[0003] In sulfide solid electrolyte systems, Na 3+δ MS4-type materials (M = P, Sb, Sn, Ge, etc., Group IV / V main elements) have attracted attention due to their highly symmetric crystal structure and excellent ion transport channels. Among them, Na3PS4 glass-ceramics and Na3SbS4 exhibit room-temperature sodium ion conductivity of approximately 10⁻⁶. -4 S / cm and 10 -3 S / cm level. Recent studies have shown that through high-valence cations (such as W...) 6+ Partial substitution at the M site can introduce sodium ion vacancies, optimize the crystal structure, and significantly improve ionic conductivity—for example, tungsten (W)-doped Na... 2.88 Sb 0.88 W 0.12 S4 has an electrical conductivity of up to 10. -1 S / cm level; Na 2.85 P 0.85 W 0.15 S4 has a conductivity of 8.8 × 10⁻⁶ at 25 °C. -3 S / cm. This doping strategy has become an important approach to improve the performance of sulfide solid electrolytes.
[0004] However, the synthesis of existing W-doped sulfide solid electrolytes mainly relies on high-energy ball milling, which has inherent drawbacks such as high energy consumption, poor batch stability, and difficulty in scaling up. Liquid-phase synthesis is considered an ideal alternative due to its advantages such as low energy consumption, good product uniformity, and ease of scale-up production. However, current liquid-phase synthesis of sulfide solid electrolytes is mainly limited to binary / ternary systems such as Li3PS4 and Na3PS4, which cannot simultaneously dissolve multiple metal sulfide precursors and cannot achieve doping with high-valence metal elements.
[0005] Therefore, existing technologies still need to be improved and developed. Summary of the Invention
[0006] In view of the shortcomings of the prior art, the purpose of this invention is to provide a high-valence cation-doped sulfide solid electrolyte and its liquid-phase synthesis method and application, aiming to solve the problems of high energy consumption, poor composition uniformity and difficulty in complete solid dissolution of high-valence cations in existing synthesis methods.
[0007] The technical solution of the present invention is as follows: A liquid-phase synthesis method for a high-valence cation-doped sulfide solid electrolyte includes the following steps: According to the chemical formula Na 3+δ M 1-x A x S4 is prepared by weighing Na2S, a sulfide containing element M, and elemental A or a sulfide containing element A, mixing and grinding them to obtain a premixed powder; wherein M is a group IV element and / or a group V element; and A is a metal element with a +5 or +6 valence. The premixed powder is mixed with a mixed solvent of organic amine and thiol, and then synthesized in the liquid phase to obtain a mixed solution; The solvent is removed from the mixed solution to obtain the precursor powder; The precursor powder was subjected to heat treatment to obtain a high-valence cation-doped sulfide solid electrolyte.
[0008] The liquid-phase synthesis method for the high-valence cation-doped sulfide solid electrolyte, wherein M is selected from one or more of P, Sb, Sn, Ge, Si, As, Se, and Te; and A is selected from one or more of W, Mo, Ta, Nb, and V.
[0009] The liquid-phase synthesis method for the high-valent cation-doped sulfide solid electrolyte, wherein the organic amine is an aliphatic primary amine or an aliphatic polyamine; Preferably, the organic amine contains at least two amino groups; Preferably, the organic amine has a base dissociation constant with a negative logarithm of less than 5 and a boiling point between 100°C and 200°C.
[0010] The liquid-phase synthesis method for the high-valent cation-doped sulfide solid electrolyte, wherein the organic amine is selected from one or more of ethylenediamine, 1,2-propanediamine, 1,3-propanediamine, diethylenetriamine, and triethylenetetramine.
[0011] The liquid-phase synthesis method for the high-valent cation-doped sulfide solid electrolyte, wherein the thiol contains at least one mercapto group; Preferably, the thiol is a C2-C4 alkyl monothiol or alkyl dithiol; Preferably, the negative logarithm of the acid dissociation constant of the thiol is between 10 and 11.
[0012] The liquid-phase synthesis method for the high-valent cation-doped sulfide solid electrolyte, wherein the thiol is selected from one or more of ethanethiol, ethylenedithiol, 1,2-propanedithiol, 1,3-propanedithiol, propanethiol, butanethiol, and thiophenol.
[0013] The liquid-phase synthesis method for the high-valent cation-doped sulfide solid electrolyte, wherein the volume ratio of the organic amine to the thiol is 10:0.5-10:3.
[0014] The liquid-phase synthesis method for the high-valent cation-doped sulfide solid electrolyte, wherein the liquid-phase synthesis temperature is 25℃-80℃ and the liquid-phase synthesis time is 2h-24h; The heat treatment temperature is 350℃-550℃, and the heat treatment time is 1h-8h.
[0015] A high-valent cation-doped sulfide solid electrolyte is prepared by a liquid-phase synthesis method for the high-valent cation-doped sulfide solid electrolyte.
[0016] Application of a high-valence cation-doped sulfide solid electrolyte in all-solid-state sodium batteries.
[0017] Beneficial effects: This invention provides a high-valence cation-doped sulfide solid electrolyte and its liquid-phase synthesis method and application. The liquid-phase synthesis method of the high-valence cation-doped sulfide solid electrolyte includes the following steps: according to the chemical formula Na... 3+δ M 1- x A x S4 is prepared by weighing Na2S, a sulfide containing element M, and elemental A or a sulfide containing element A in stoichiometric proportions. After mixing and grinding, a premixed powder is obtained; wherein M is a Group IV element and / or a Group V element; and A is a +5 or +6 valence metal element. The premixed powder is then mixed with a mixed solvent of organic amine and thiol, and synthesized in the liquid phase to obtain a mixed solution. The solvent is removed from the mixed solution to obtain a precursor powder. The precursor powder is then heat-treated to obtain a tungsten-doped sulfide solid electrolyte. This invention uses a mixed solvent of organic amine and thiol as a high-valence cation to dope Na. 3+δThe MS4 liquid-phase synthesis solvent system utilizes organic amines to induce the deprotonation of thiols, generating nucleophilic thiolate anions. These thiolate anions, with their high nucleophilicity, attack the MS and AS bonds in metal sulfides, causing the original bonds to break and dissociate into soluble complexes. The protonated amine cations act as counterions, stabilizing the soluble complexes. In this mixed solvent, cross-coordination reactions occur between the polyanions generated from the dissociation of different metal sulfides, forming more complex heteropolythiometallic anions, further enhancing the synergistic effect of the solubility of each component. After solvent removal and heat treatment, a high-valence cation-doped sulfide solid electrolyte is obtained. This method is energy-efficient, simple, produces high-purity products, exhibits good uniformity of high-valence cation doping, and leaves no sulfide residue. The resulting electrolyte achieves a sodium ion conductivity of up to 10 at room temperature. -3 S cm -1 This level is suitable for large-scale production. Attached Figure Description
[0018] Figure 1 This is a process flow diagram of a liquid-phase synthesis method for a high-valence cation-doped sulfide solid electrolyte according to the present invention; Figure 2 Na prepared in Example 1 2.85 P 0.85 W 0.15 S4 elemental surface distribution map using scanning electron microscopy; Figure 3 Na prepared for Comparative Example 2 2.85 P 0.5 W 0.15 S4 elemental surface distribution map using scanning electron microscopy; Figure 4 The XRD patterns are of the solid electrolytes prepared in Example 2 and Comparative Example 3. Figure 5 Na prepared in Example 1 2.85 P 0.85 W 0.15 Particle size distribution diagram of S4; Figure 6 Na prepared for Comparative Example 1 2.85 P 0.5 W 0.15 Particle size distribution diagram of S4. Detailed Implementation
[0019] This invention provides a high-valence cation-doped sulfide solid electrolyte, its liquid-phase synthesis method, and its application. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the invention is further described in detail below. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0020] It will be understood by those skilled in the art that, unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. It should also be understood that terms such as those defined in general dictionaries should be understood to have the same meaning as in the context of the prior art, and should not be interpreted in an idealized or overly formal sense unless specifically defined as herein.
[0021] The high-energy ball milling method for synthesizing W-doped sulfide solid electrolytes is currently the most advanced method for preparing Na+. 3+δ M 1-x W x The standard method for S4 type electrolytes involves mixing raw materials such as Na2S, P2S5 (or Sb2S3, etc.), and WS2 in stoichiometric ratios and placing them in a ball mill jar. High-energy ball milling is then performed for tens of hours under an inert atmosphere to ensure thorough mixing and amorphization. The final product is obtained through high-temperature heat treatment. However, high-energy ball milling has at least the following drawbacks: 1) Extremely high energy consumption – High-energy ball milling typically requires tens or even hundreds of hours, resulting in high equipment power and energy consumption, which does not align with green manufacturing principles; 2) Equipment wear introduces impurities – Prolonged ball milling leads to wear on the grinding media and jar, introducing impurities such as ZrO2, affecting electrolyte purity; 3) Poor batch stability – The ball milling effect is affected by various factors such as the loading amount, ball-to-material ratio, and rotation speed, resulting in large performance fluctuations between batches; 4) Limited component uniformity – Ball milling is essentially a solid-state mixing process, making it difficult to achieve atomic-level uniform doping, easily leading to localized enrichment or unreacted raw material residues; 5) Difficulty in scaling up – Laboratory-level ball mills have limited processing capacity, while industrial scale-up faces problems such as high equipment investment and low efficiency.
[0022] Existing liquid-phase methods for synthesizing undoped Na3PS4 use N-methylformamide (NMF) as a solvent to synthesize cubic Na3PS4 via liquid-phase reaction. Other studies have used 1,2-dimethoxyethane (DME) as the reaction medium to prepare Na3PS4 via a suspension method. 4-x Cl x Electrolytes; other studies have used methyl acetate to prepare cubic Na3PS4 via a liquid-phase oscillation method. However, the following drawbacks exist: 1) Extremely narrow applicability—the above methods are only applicable to Na3PS4 or Na3PS... 4-x Cl x Simple systems, without doping with high-valence metal elements such as W, because conventional solvents (NMF, DME, methyl acetate, etc.) have extremely weak or no solubility for metal sulfides such as WS2 / W2S5; 2) Low ionic conductivity—the room temperature conductivity of Na3PS4 prepared by the NMF method is only 2.6 × 10⁻⁶. -6S / cm, far lower than similar materials prepared by ball milling (approximately 10). -4 S / cm); 3) Solvent residue problem - High-boiling-point polar solvents (such as NMF with a boiling point of about 199°C) are difficult to completely remove, and residual solvents can cause side reactions in subsequent battery cycles; 4) Incomplete reaction in suspension method - In solvent systems such as DME, the raw materials exist in a suspended state, the reaction is uneven, and the conversion rate is limited.
[0023] Therefore, existing methods for synthesizing high-valent cation-doped sulfide solid electrolytes suffer from technical problems such as high energy consumption, poor compositional uniformity, difficulty in completely dissolving high-valent cations, batch instability, difficulty in scaling up, and the inability of liquid-phase methods to simultaneously dissolve multiple metal sulfide precursors.
[0024] Based on this, such as Figure 1 As shown, this invention provides a liquid-phase synthesis method for high-valent cation-doped sulfide solid electrolytes, comprising the following steps: Step S10: According to the chemical formula Na 3+δ M 1-x A x S4 is prepared by weighing Na2S, a sulfide containing element M, and elemental A or a sulfide containing element A, mixing and grinding them to obtain a premixed powder; wherein M is a group IV element and / or a group V element; and A is a metal element with a +5 or +6 valence. Step S20: The premixed powder is mixed with a mixed solvent of organic amine and thiol, and then synthesized in the liquid phase to obtain a mixed solution; Step S30: Remove the solvent from the mixed solution to obtain precursor powder; Step S40: The precursor powder is heat-treated to obtain a high-valence cation-doped sulfide solid electrolyte.
[0025] In this embodiment, a mixed solvent of organic amines and thiols is used as the high-valence cation dopant for Na. 3+δ The MS4 liquid-phase synthesis solvent system utilizes organic amines to induce the deprotonation of thiols, generating nucleophilic thiolate anions. These thiolate anions, with their high nucleophilicity, attack the MS and AS bonds in metal sulfides, causing the original bonds to break and dissociate into soluble complexes. The protonated amine cations act as counterions, stabilizing the soluble complexes. In this mixed solvent, cross-coordination reactions occur between the polyanions generated from the dissociation of different metal sulfides, forming more complex heteropolythiometallic anions, further enhancing the synergistic effect of the solubility of each component. After solvent removal and heat treatment, a high-valence cation-doped sulfide solid electrolyte is obtained. This method is energy-efficient, simple, produces high-purity products, exhibits good uniformity of high-valence cation doping, and leaves no sulfide residue. The resulting electrolyte achieves a sodium ion conductivity of up to 10 at room temperature. -3 S cm-1 grade, suitable for large-scale production.
[0026] Specifically, in the present invention, the metal element A with a valence of +5 or +6 is introduced into Na through a liquid phase method 3+δ MS4 crystal lattice, so as to realize uniform substitution of high-valent cations at the M site, and no sulfide residue containing element A exists in the product; moreover, an amine-thiol alkaline mixed solvent (i.e., a mixed solvent of organic amine and thiol) is used as a general solvent system for the liquid phase synthesis of high-valent cation doped Na 3+δ MS4, revealing the complete dissolution mechanism of "amine deprotonates thiol → thiolate anion performs nucleophilic attack to break the M—S bond → forms a soluble complex → protonated amine acts as a counterion to stabilize the complex", and this mechanism is applicable to both sulfides containing element M and sulfides containing element A, with regularity and universality. At the same time, complete solid solution of high-valent cations is realized through uniform mixing at the liquid phase molecular level. The ball milling method is difficult to avoid the residue of sulfides containing element A, while the liquid phase method realizes atomic-level uniform substitution of the element corresponding to the high-valent cation in the crystal lattice through the path of complete precursor dissolution-uniform precipitation.
[0027] In some embodiments, M is selected from one or more of P, Sb, Sn, Ge, Si, As, Se and Te; the above M elements can be flexibly selected from a plurality of main group sulfur-affine elements for single-component or multi-component solid solution regulation, and the lattice defect concentration and crystal symmetry can be precisely regulated through aliovalent substitution, so as to realize controllable phase transition between the tetragonal phase and the cubic phase, further widen the size of the sodium ion diffusion bottleneck, and achieve both high ionic conductivity and structural thermodynamic stability.
[0028] In some embodiments, in the chemical formula Na 3+δ M 1-x A x S4, 0<x≤0.2, and δ is determined by valence balance; preferably, 0.05≤x≤0.20; more preferably, 0.05≤x≤0.15.
[0029] In some embodiments, M is selected from at least two of P, Sb, Sn, Ge, Si, As, Se and Te for composite doping, such as P / Sb co-doping: Na3P 0.4 Sb 0.4 W 0.15 S4, the co-doping of two or more M elements can synergistically optimize the three core indicators of ionic conductivity, air stability and interfacial compatibility, and solve the performance shortboard of a single system.
[0030] In a preferred embodiment, M is selected from one or more of P, Sb, Sn and Ge. The sulfide containing element M is one or more of P2S5, Sb2S3, SnS2 and GeS2.
[0031] In some embodiments, A is selected from one or more of W, Mo, Ta, Nb, and V. All of the above-mentioned A elements can lower the Na vacancy formation energy and increase electrical conductivity. For AS bonds with high breaking energy barriers (where A is one of W, Mo, Ta, Nb, or V), the thiol ratio can be increased.
[0032] In a preferred embodiment, tungsten (W) is selected as a high-valent cation to achieve the reaction of Na+ with Na+. 3+δ MS4 doping. Elemental A and / or sulfides containing elemental A are one or more of elemental W, WS2, and W2S5.
[0033] In some embodiments, the organic amine is an aliphatic primary amine or an aliphatic polyamine; the amino group in the aliphatic primary amine or aliphatic polyamine has Lewis basicity and can abstract a proton from the thiol group (-SH), resulting in an acid-base proton transfer reaction.
[0034] In some embodiments, the organic amine contains at least two amino groups (-NH2), wherein the first amino group, as a Lewis base, can abstract a proton from the thiol group (-SH) in the thiol molecule, thereby deprotonating the thiol to generate a highly nucleophilic thiolate anion (R′-S). - This is the key active substance for dissolving metal sulfides; the second amino group (and other amino groups in polyamines) can further form a multi-point hydrogen bond network with the metal sulfide polyanions and protonated amine cations generated by dissociation, thereby enhancing the stability of the soluble complex in solution.
[0035] In some embodiments, the organic amine has a negative logarithm of its base dissociation constant (pKb) less than 5 and a boiling point between 100°C and 200°C. A suitable pK difference between the basicity of the organic amine (pKb < 5) and the acidity of the thiol (pKa 10-11) ensures the thermodynamic spontaneity and kinetic rate of the deprotonation reaction, allowing the metal sulfide to completely dissolve within seconds to hours.
[0036] In some embodiments, the organic amine is selected from one or more of ethylenediamine (EDA), 1,2-propanediamine, 1,3-propanediamine, diethylenetriamine, and triethylenetetramine. The aforementioned organic amines possess sufficient basicity (pKb < 5) to ensure effective deprotonation of thiols.
[0037] In a preferred embodiment, the organic amine is a primary amine such as ethylenediamine or 1,2-propanediamine.
[0038] In some embodiments, the thiol contains at least one mercapto group (-SH); the thiol anion (R′-S) is generated by deprotonation of the mercapto group with an organic amine. -It has extremely high nucleophilicity and can perform nucleophilic attacks on the MS bonds in metal sulfides (such as P2S5, Sb2S3, SnS2, GeS2, WS2, etc.). The MS bonds are broken through the addition-elimination mechanism to generate soluble polythiometallic anion complexes.
[0039] In some embodiments, the thiol is a C2-C4 alkyl monothiol or alkyl dithiol; when an alkyl dithiol (such as ethylene dithiol) is used, its dithiol structure can provide two nucleophilic sites, further enhancing the solubility of high-valent metal sulfides (such as WS2, GeS2, etc.); when a low-boiling-point alkyl monothiol (such as ethylene mercaptan, boiling point 35°C) is used, it is beneficial to reduce carbon residue during subsequent solvent removal, balancing solvent efficiency and product purity.
[0040] In some embodiments, the thiol has a negative logarithm (pKa) of acid dissociation constant between 10 and 11, and the thiol has a low boiling point, which is beneficial for removal to reduce carbon residue.
[0041] In some embodiments, the thiol is selected from one or more of ethanethiol (ET), ethylenedithiol (EDT), 1,2-propanedithiol, 1,3-propanedithiol, propanethiol (boiling point 67°C), butanethiol (boiling point 98°C), and thiophenol. The thiol is selected based on a pKa between 10 and 11 and a boiling point as low as possible.
[0042] In this embodiment, the matching mechanism of the mixed solvent formed by the organic amine and the thiol is analyzed, including: 1) Amine-induced deprotonation of thiols to generate nucleophilic thiolate anions Amine solvents (such as ethylenediamine EDA, kPb≈4.0) have Lewis basicity, which allows them to abstract a proton from the thiol group (-SH) in thiols (such as ethanethiol ET, pKa≈10.6), resulting in an acid-base proton transfer reaction: R-NH2 + R′-SH → R-NH 3+ +R′-S - The thermodynamic driving force of this reaction comes from the pK difference between the basicity of the amine and the acidity of the thiol. Taking ethylenediamine as the organic amine and ethylenedithiol as the thiol as an example, DFT (density functional theory) calculations show that the energy of proton transfer from EDT to EDA in the EDA-EDT system is -0.61 eV, indicating that the process is spontaneous; the generated thiol anion (R′-S - The sulfur atom in thiols carries a negative charge, significantly enhancing nucleophilicity (by approximately 10% compared to neutral thiols). 3 (times), becoming a key active substance for dissolving metal sulfides.
[0043] 2) Nucleophilic attack and cleavage of MS bonds by thiol anions The high nucleophilicity of thiolate anions enables them to perform nucleophilic attacks on MS bonds (such as Ge-S, Sn-S, PS, WS, etc.) in metal sulfides; taking WS2 as an example, the reaction process can be represented as: WS2 + 2R′-S - →[(R′-S)2W=S] 2- The reaction mechanism follows an addition-elimination pathway: the lone pair of electrons of the thiol anion attacks the σ* antibonding orbital of the WS bond in WS2, forming a five-coordinate transition state. Subsequently, the original WS bond breaks, and the thiol anion forms a new WS bond with the W atom, ultimately causing the WS2 crystal to dissociate into a soluble polythiotungstate anion complex. The dissolution of GeS2 in EDA-EDT solvent is completed within seconds, confirming the extremely fast kinetics of this nucleophilic attack. The nucleophilicity of the thiol anion is significantly reduced in protic solvents due to protonation; therefore, choosing aprotic or weakly protic amine solvents is crucial.
[0044] 3) Protonated amines as stable soluble complexes against cations During the dissolution process, protonated amine cations (such as EDA·H) + As a counter ion, it forms stable ion pairs with the polyanions of the metal sulfides generated by dissociation, promoting a rightward shift in the dissolution equilibrium of metal sulfides in organic solvents. The resulting solution is a homogeneous and transparent solution, indicating the formation of a true molecular-level solution.
[0045] Synergistic dissolution effect: When Na2S, P2S5 (or Sb2S3, etc.) coexist with WS2 in EDA-ET mixed solvent, cross-coordination reactions occur between the polyanions generated by the dissociation of different metal sulfides, forming more complex heteropolythiometallic anions (such as [PWS2]). x ] n- This further enhances the synergistic effect of the solubility of each component. This is also the fundamental reason why a single solvent is not effective at dissolving each component individually, while a mixed solvent can completely dissolve all precursors simultaneously.
[0046] In some embodiments, the volume ratio of the organic amine to the thiol is 10:0.5-10:3. Preferably, the volume ratio is 10:1-10:2. If the ratio is too low, the concentration of thiol anions is insufficient, resulting in incomplete dissolution; if the ratio is too high, carbon residue increases significantly. When the volume ratio of organic amine to thiol exceeds 10:4, the mixed solvent may solidify. Furthermore, the polarity of the solvent affects the stability of the intermediate complex and the crystallinity of the product. The mixed solvent system obtained by mixing organic amine and thiol has moderate polarity, and the polarity can be fine-tuned by adjusting the ratio of organic amine to thiol; the higher the polarity, the more stable the intermediate complex and the higher the crystallinity of the product.
[0047] In some embodiments, in step S20, the premixed powder is mixed with a mixed solvent of organic amine and thiol, such that the concentration of the resulting solution is 30 mg / ml-60 mg / ml. If the concentration is too low, the solution system is unstable, the precipitated product has too small a particle size and low yield; if the concentration is too high, the dissolution is insufficient, and unreacted precursors (i.e., premixed powder) remain.
[0048] In some embodiments, the liquid-phase synthesis temperature is 25°C-80°C, and the liquid-phase synthesis time is 2h-24h; the liquid-phase reaction occurs by heating the solution after mixing the premixed powder with a mixed solvent of organic amine and thiol; when the temperature is too low, the dissolution kinetics are slow and the reaction time is prolonged; when the temperature is too high, the solvent volatilization is aggravated and the system is unstable.
[0049] In a preferred embodiment, the temperature of the liquid phase synthesis is 50°C-70°C, and the time of the liquid phase synthesis is 4h-12h.
[0050] In some embodiments, in step S20, the liquid phase reaction stage of liquid phase synthesis can be replaced by microwave heating (300W-800W). By utilizing the selective heating and dipole polarization effect of microwaves, the reaction time can be shortened to 15min-60min.
[0051] In some embodiments, in step S30, the solvent in the mixed solution is removed by spray drying; the mixed solution after liquid phase reaction is directly granulated by spray drying, which improves the uniformity of the precursor and the production efficiency, and the rapid evaporation of the solvent during spraying can reduce the decomposition of the complex.
[0052] In some embodiments, the liquid-phase synthesis in step S20 and the solvent removal in step S30 can be completed in one step using a continuous flow process; the liquid-phase reaction and solvent removal are integrated into a continuous flow reactor to achieve continuous production.
[0053] In some embodiments, in step S30, the solvent in the mixed solution can be removed by freeze drying; this method is suitable for heat-sensitive systems and can better preserve the structure of the precursor complex.
[0054] In some embodiments, the heat treatment temperature is 350°C-550°C, and the heat treatment time is 1h-8h.
[0055] Specifically, when M=P, the stable phase of the Na3PS4-based electrolyte is a tetragonal or cubic phase, with a relatively high crystallization temperature, and the preferred heat treatment temperature is 480℃-550℃; when M=Sb, the thermal stability of the Na3PS4-based electrolyte is relatively low, and the preferred heat treatment temperature is 420℃-480℃; when M=Sn or Ge, the corresponding electrolyte has a relatively high crystallization temperature, and the preferred heat treatment temperature is 500℃-550℃; the holding time is 2h-6h for all cases.
[0056] In addition, the present invention also provides a high-valence cation-doped sulfide solid electrolyte, which is prepared by a liquid-phase synthesis method of the high-valence cation-doped sulfide solid electrolyte.
[0057] In addition, the present invention also provides the application of a high-valence cation-doped sulfide solid electrolyte in an all-solid-state sodium battery.
[0058] In some embodiments, the mixed solution obtained in step S20 is directly mixed with the positive electrode active material (such as TiS2, NaCrO2, etc.), and an electrolyte coating layer is formed on the surface of the active material through in-situ precipitation, which improves the three-phase interface contact and realizes the preparation of composite positive electrode.
[0059] In some embodiments, based on electrolyte slurry coating, the mixed solution obtained in step S20 is directly coated onto the substrate, and then heat-treated to form a large-area solid electrolyte film.
[0060] In some embodiments, based on the electrolyte-injected porous electrode, the electrolyte is injected into the porous electrode using the low viscosity characteristics of the mixed solution obtained in step S20, and a three-dimensional ion-conducting network is formed after in-situ reaction and heat treatment.
[0061] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention.
[0062] Example 1 This embodiment provides an EDA-ET solution-based liquid-phase synthesis of Na. 2.85 P 0.85 W 0.15 S4, the specific steps are as follows: Step (1) Raw material pretreatment: In an inert atmosphere glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), Na2S (purity ≥ 99%), P2S5 (purity ≥ 99%), and WS2 (purity ≥ 99%) were accurately weighed according to the stoichiometric ratio, controlling the Na:P:W molar ratio to be 2.85:0.85:0.15. The raw materials were then manually ground in an agate mortar for 20 min to obtain a premixed powder.
[0063] Step (2) Liquid phase reaction: Prepare a mixed solvent with a volume ratio of EDA to ET of 10:2. Add the premixed powder to the mixed solvent, and control the total concentration of the raw materials to 40 mg / mL. Stir the mixture magnetically at 60℃ for 6 hours to completely dissolve the raw materials and form a dark brown transparent solution.
[0064] Step (3) Solvent removal: Transfer the reaction solution to a vacuum drying oven and dry it for 12 h at 100℃ and a vacuum degree ≤ -0.09 MPa to allow the solvent to evaporate completely and collect the precursor powder.
[0065] Step (4) High-temperature heat treatment: Spread the precursor powder evenly in a crucible and gently press it compact. Place it in a tube furnace and heat it to 500℃ at a rate of 5℃ / min under the protection of flowing high-purity Ar gas. Hold it at this temperature for 4 h and then cool it to room temperature with the furnace to obtain Na. 2.85 P 0.85 W 0.15 S4.
[0066] Technical effect: The obtained Na 2.85 P 0.85 W 0.15 The S4 electrolyte has an ionic conductivity of up to 8.7 × 10⁻⁶ at room temperature. -3 S cm -1 The W element is uniformly distributed in the crystal lattice, with no WS2 residue.
[0067] Example 2 This embodiment provides an EDA-ET solution-based liquid-phase synthesis of Na. 2.9 Sb 0.9 W 0.1 S4, the specific steps are as follows: Step (1) Raw material pretreatment: Same as in Implementation Method 1, weigh Na2S, Sb2S3 (purity ≥99%) and WS2 according to the stoichiometric ratio, with a molar ratio of Na:Sb:W = 2.9:0.9:0.1.
[0068] Step (2) Liquid phase reaction: A mixed solvent of EDA and ET with a volume ratio of 10:1 was used. The raw material concentration was 40 mg / mL. The mixture was stirred at 60℃ for 6 h to obtain an orange-yellow transparent solution.
[0069] Step (3) Solvent removal: Same as in Example 1, vacuum drying at 100℃ for 12 h.
[0070] Step (4) High temperature heat treatment: Heat to 450℃ at 5℃ / min under Ar atmosphere, hold for 3 h, and cool with the furnace.
[0071] Technical effect: The obtained Na 2.9 Sb 0.9 W 0.1 S4 has an ionic conductivity of up to 6.2 × 10⁻⁶ at room temperature. -3 S cm -1 It exhibits good stability against sodium metal.
[0072] Example 3 This embodiment provides an EDA-EDT solution-based liquid-phase synthesis of Na. 2.9 Sn 0.9 W 0.1 S4, the specific steps are as follows: Step (1) Raw material pretreatment: Same as in Example 1, weigh Na2S, SnS2 (purity ≥99%) and WS2, with a molar ratio of Na:Sn:W = 2.9:0.9:0.1.
[0073] Step (2) Liquid phase reaction: A mixed solvent of EDA and EDT with a volume ratio of 10:1 was used, and the raw material concentration was 30 mg / mL. The mixture was stirred at 70℃ for 12 h to obtain a yellow transparent solution.
[0074] Step (3) Solvent removal: Vacuum dry at 110℃ for 18 h.
[0075] Step (4) High temperature heat treatment: Under Ar atmosphere, the temperature is increased to 520℃ at 5℃ / min, held for 5 h, and then cooled with the furnace.
[0076] Technical advantages: EDT has stronger nucleophilicity, ensuring complete dissolution of SnS2 and WS2. The resulting Na... 2.9 Sn 0.9 W 0.1 The S4 electrolyte can achieve an ionic conductivity of 4.1 × 10⁻⁶ at room temperature. -3 S cm -1 High-temperature heat treatment can effectively reduce carbon residue (<1 wt%).
[0077] Comparative Example 1 This comparative example utilizes high-energy ball milling to prepare Na 2.85 P 0.5 W 0.15 S4, the specific steps are as follows: Step (1) Weighing raw materials: In an Ar atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), accurately weigh Na2S (purity ≥99%), P2S5 (purity ≥99%) and WS2 (purity ≥99%) according to the stoichiometric ratio.
[0078] Step (2) Solid-phase reaction: After weighing and mixing the raw materials, place them in a 50 mL ZrO2 ball mill jar, add ZrO2 grinding balls with a diameter of 10 mm, and control the ball-to-material mass ratio to be 20:1. After sealing the ball mill jar, remove it from the glove box and place it in a planetary ball mill. Grind at 600 rpm for 40 h, pausing for 15 min every 1 h to prevent the jar from overheating.
[0079] Step (3) Zirconium bead removal: After ball milling, the ball mill jar is moved back to the glove box and the ZrO2 balls and powder products are separated by sieving.
[0080] Step (4) High temperature heat treatment: Spread the obtained powder evenly in an alumina crucible and press it firmly. Place it in a tube furnace and heat it to 500°C at a rate of 5°C / min under the protection of flowing high-purity Ar gas (flow rate 100 mL / min). Hold it at this temperature for 4 h and then cool it to room temperature with the furnace to obtain the comparative product.
[0081] Comparative Example 2 This comparative example utilizes a single acetonitrile (ACN) solvent to synthesize Na in liquid phase. 2.85 P 0.5 W 0.15 S4, the specific steps are as follows: Step (1) Raw material pretreatment: The same raw material ratio as in Example 1: Accurately weigh 0.222 g (2.85 mmol) of Na2S, 0.189 g (0.85 mmol) of P2S5 and 0.037 g (0.15 mmol) of WS2, and grind by hand for 20 min to obtain premixed powder.
[0082] Step (2) Liquid-phase reaction: The premixed powder was added to 10 mL of anhydrous acetonitrile (ACN, purity 99.9%, H2O < 50 ppm), and the total concentration of the raw materials was controlled at 40 mg / mL. The reaction was carried out under magnetic stirring at 60℃ for 6 h. During the experiment, it was observed that the mixture was always in a black suspension, and the black WS2 powder clearly sank to the bottom of the bottle, failing to form a transparent solution.
[0083] Step (3) Solvent removal: After the reaction is completed, the suspension is transferred to a vacuum drying oven and dried at 80°C and vacuum degree ≤ -0.09 MPa for 12 h to allow the acetonitrile to completely evaporate and the precursor powder is collected.
[0084] Step (4) High-temperature heat treatment: The precursor powder is placed in a tube furnace and heated to 500℃ at 5℃ / min under Ar atmosphere and held for 4 h. The product is obtained by cooling with the furnace.
[0085] Comparative Example 3 This comparative study investigates the effect of inappropriate heat treatment temperature on the liquid-phase synthesis of Na. 2.9 Sb 0.9 W 0.1 The effects of S4 are explained in the following steps: Step (1) Raw material pretreatment: In an Ar atmosphere glove box, using the same raw material ratio and liquid phase reaction conditions as in Example 2: accurately weigh 0.226 g (2.9 mmol) of Na2S, 0.306 g (0.9 mmol) of Sb2S3 and 0.025 g (0.1 mmol) of WS2, and grind by hand for 15 min.
[0086] Step (2) Liquid phase reaction: Add the premixed powder to 10 mL of EDA-ET mixed solvent (volume ratio 10:1), stir at 60℃ for 6 h to obtain an orange-yellow transparent solution.
[0087] Step (3) Solvent removal: Vacuum drying at 100℃ for 12 h to obtain precursor powder.
[0088] Key difference step (4): The precursor powder is placed in a tube furnace and heated to 550°C at 5°C / min under an Ar atmosphere (instead of 450°C in Example 2), held for 3 h, and cooled with the furnace to obtain the product.
[0089] The particle size D50, ionic conductivity, and carbon residue of the products obtained in Examples 1-3 and Comparative Examples 1-3 were characterized, and the specific data are shown in Table 1. The electrolyte powder was tested in a glove box, and the specific testing method for ionic conductivity was as follows: 1) Sample preparation The electrolyte powder is cold-pressed into sheets at a pressure of 360–500 MPa, with a thickness of approximately 0.1–1 mm and a diameter of 10–14 mm. The thickness is measured using a micrometer.
[0090] 2) Electrochemical impedance spectroscopy (EIS) The sample is held in place using a blocking electrode (such as stainless steel or sputtered metal film), and an AC voltage (amplitude 10mV, frequency range 1MHz to 0.1Hz) is applied.
[0091] The bulk resistance Rbulk is obtained by fitting the semicircular intercept in the high-frequency region using EIS, while the low-frequency region reflects the interfacial resistance and the double-layer effect.
[0092] 3) Geometric parameter measurement Thickness (LL): The thickness of the compressed tablet is measured directly using a micrometer; Area (AA): Calculated based on the electrode diameter; According to the formula Calculate the ionic conductivity of the corresponding material.
[0093] Table 1
[0094] The solid electrolytes prepared in Example 1 and Comparative Example 2 were characterized at the microscopic level. The Na₂O₃ prepared in Example 1... 2.85 P 0.85 W 0.15 The elemental mapping diagram of S4 using scanning electron microscopy is shown below. Figure 2 As shown, W element is uniformly distributed and adheres to the particle surface, playing a role; the Na prepared in Comparative Example 2 2.85 P 0.5 W 0.15 The elemental distribution diagram of S4 using scanning electron microscopy is shown below. Figure 3 As shown, the distribution of W element is extremely uneven and the bright spots of W element are relatively small. Figure 2 It is relatively dense and shows signs of dissolution.
[0095] The scanning electron microscope imaging method is as follows: 1) Sample preparation (core step of inert gas protection) Pretreatment environment: The entire process is carried out in an Ar gas glove box (O2 / H2O content ≤0.1 ppm) to avoid exposing the sample to air.
[0096] Sample type adaptation: bulk / sintered sheet; Powder sample: Fix the silicon wafer to the sample stage with conductive adhesive, and spray the powder sample onto the surface of the conductive adhesive; 2) Instrument preparation and vacuum optimization Instrument selection: SEM: Field emission scanning electron microscope (FE-SEM), resolution ≥1nm; EDS detector: Silicon drift detector (SDD), energy resolution ≤129eV.
[0097] Instrument warm-up and calibration: Turn on the SEM host, EDS system and vacuum system, and preheat for 30 minutes; EDS energy calibration: Calibrate using standard samples to ensure accurate positions of the characteristic peaks S (2.31 keV) and P (2.01 keV); Vacuum requirement: Sample chamber vacuum ≥ 1×10 -4 Pa.
[0098] Sample transfer and installation: Use a sealed sample transfer box (fill the sample into the glove box and then seal it) to reduce exposure time (≤30 seconds); Quickly place the sample stage into the SEM sample chamber, ensuring that the center of the sample is aligned with the electron beam scanning area; Close the sample chamber door and start the vacuum process (wait 15 minutes until the vacuum indicator light turns green).
[0099] 3) SEM parameter optimization (adapting to LPSC insulation + easy hydrolysis characteristics) Morphological observation and regional location: Magnification: First observe the overall morphology at low magnification (100×) to confirm that there is no hydrolysis (no white flocculent deposits) and no fragmentation; Then adjust to medium-high magnification (2000×) and select a flat area without pores / cracks as the ROI; Accelerating voltage: 12kV (a key parameter to balance signal strength and sample stability). Working distance: 10mm (balancing signal strength and spatial resolution); Beam current: 3nA (to ensure signal strength while avoiding sample damage); Manually optimize focus and astigmatism to ensure clear images of the ROI area (no blur or ghosting).
[0100] Charge accumulation suppression measures: If charge accumulation still occurs, reduce the accelerating voltage to 9kV, increase the beam current to 4nA, or turn on the "low vacuum mode" (vacuum degree 15Pa) of the SEM.
[0101] 4) EDS Mapping Parameter Settings (for LPSC element characteristics) Element channel selection: Required elements: Li (Kα, 0.05keV), P (Kα, 2.01keV), S (Kα, 2.31keV), Ge (Lα, 9.89keV, if present); Optional element: O (Kα, 0.52keV, used to determine whether the sample is hydrolyzed).
[0102] Key acquisition parameter settings: Pixel dwell time: 15ms / pixel (Li element signal is weak, requiring sufficient time); Scan resolution: 1024×1024 pixels (to ensure detailed element distribution); Count rate control: Target 3000 cps (counts per second); Acquisition mode: "Net Map" (net count mode), automatically removes background noise.
[0103] Pre-scan before data acquisition: Perform two rapid pre-scans of the ROI region (dwell time 5ms) and observe the count rate of each element; If the Li element count rate is <50 cps, adjust the parameters (extend the residence time to 18 ms or increase the beam current to 4 nA). If no significant peak overlap is confirmed, adjust the element channel energy window if necessary.
[0104] 5) Mapping data acquisition and monitoring Start data collection: In the EDS software, click "Mapping" → "Start Data Acquisition" and record the current parameters; Acquisition time: Approximately 20 minutes (1024×1024 pixels, 15ms / pixel); Real-time monitoring: Count rate curve: Remains stable between 2000 and 4000 cps; SEM images: If increased charge accumulation or whitening of the sample surface (signs of hydrolysis) is observed, terminate the test immediately.
[0105] Data collection complete: Save the original data (.azt / .emd format) and export the element distribution image; Close the EDS acquisition interface, but keep the SEM image interface open to observe the sample status.
[0106] 6) Data Analysis and Precautions Key aspects of data analysis: Qualitative analysis: Confirm whether the distribution of Li, P, S, and Ge is uniform, and observe the distribution of O element to determine whether hydrolysis has occurred; Semi-quantitative analysis: Comparison of P, S, and Ge signal intensities in different regions to assess the uniformity of distribution (Li is only used for qualitative judgment); Data processing: background subtraction, adjusting image contrast to highlight differences in element distribution, and superimposing P and S element images to observe co-distribution.
[0107] The solid electrolytes prepared in Example 2 and Comparative Example 3 were characterized by their phase composition, and their XRD patterns are shown below. Figure 4 As shown, compared with Example 2, Comparative Example 3 caused Sb2S3 to partially decompose due to excessively high sintering temperature, generating Na2S impurity phase.
[0108] The phase testing methods are as follows: 1) Sample preparation: Powder sample preparation Grinding requirements: The sulfide powder must be ground to a uniform particle size (passing through a 200-mesh sieve, particle size ≤75μm), with no grainy feel to the touch, similar to the texture of flour, in order to reduce preferred orientation and enhance the intensity of diffraction peaks.
[0109] Moisture-proof treatment: Sulfides are prone to moisture absorption and decomposition, so they need to be ground and pressed in an inert gas (such as argon) glove box to avoid oxidation or structural damage.
[0110] Compressing method: The positive pressure method is used to fill the powder into the groove of the glass sample holder and compact it with a glass plate until the surface is flat and flush with the groove to ensure sample uniformity.
[0111] 2) Instrument setup and testing procedures Instrument initialization Circulating water system: Ensure water temperature is 17-20℃ and water pressure is 0.3-0.4MPa to prevent equipment from overheating or being damaged.
[0112] Software startup: Open the PC-based XRD control software (such as Rigaku Ultimate IV or DIFFRAC measurement system), initialize the goniometer, and confirm that the sample chamber door is closed.
[0113] Parameter settings Scanning range: standard wide-angle test range 5°-90°, step size 0.02°, scanning speed 5° / min (adjusted according to sample crystallinity).
[0114] Slit width: entrance slit 0.2-0.6mm, detector slit 3-8mm, optimizing resolution and signal-to-noise ratio.
[0115] X-ray conditions: copper target Kα rays (λ=1.5418 Å), voltage 40 kV, current 30 mA, to ensure clear diffraction peaks.
[0116] Sample loading and testing Sample loading procedure: Gently open the sample chamber door, insert the sample holder into the slot, ensuring the sample surface is facing up and centered, gently close the door and confirm that the closing indicator light is on.
[0117] Start the test: Click "Start" to start the scan. Wait for the software to indicate that the scan is complete and save the data (e.g., RAW or TXT format).
[0118] The particle size distribution of the solid electrolytes prepared in Example 1 and Comparative Example 1 was characterized. The Na prepared in Example 1... 2.85 P 0.85 W 0.15 The particle size distribution diagram of S4 is as follows: Figure 5 As shown, Na prepared in Comparative Example 1 2.85 P 0.5 W 0.15 The particle size distribution diagram of S4 is as follows: Figure 6 As shown; by Figure 5 and Figure 6 It can be seen that there is a difference in particle size distribution between the electrolyte powder synthesized by different processes in Example 1 and Comparative Example 1.
[0119] The steps for dry testing of particle size distribution using a laser particle size analyzer include: 1) Powder Sample Preparation Grinding Requirements: Sulfide powder should be gently ground until loose and free of lumps. Over-grinding should be avoided to prevent particle breakage and lattice damage. Compaction is strictly prohibited throughout the process; the powder should be kept in a naturally loose state to ensure representativeness of the test. Moisture Protection: Sulfides are prone to absorbing moisture and decomposing, releasing hydrogen sulfide. Therefore, the entire sample loading process must be completed in an inert gas (argon) glove box, controlling the water and oxygen content to ≤0.1ppm to prevent hydrolysis and oxidation that could lead to particle size distortion. Sample Loading Method: Gently add the powder to be tested into the dry sample cell, tapping it several times to ensure even distribution and preventing bridging, air bubbles, and stratification.
[0120] 2) Instrument setup and testing procedures (1) Instrument initialization Gas source check: Ensure the pressure of dry compressed air / inert gas is stable at 0.1-0.3 MPa, guaranteeing a stable, oil-free, and water-free dispersion airflow. Instrument warm-up: Turn on the laser particle size analyzer main unit and the computer-based testing software, and warm up for 15-30 minutes to ensure optical path stability and baseline zeroing. Background calibration: Close the sample chamber door and perform background and optical path calibration to ensure background noise is below the threshold.
[0121] (2) Parameter settings Test mode: Dry dispersion mode; Test range: 0.01-100μm; Dispersion pressure: 0.05-0.15 MPa (low pressure, weak dispersion, to avoid particle breakage); Number of tests: 3 repetitions, average value as the final result; Scan time: 10-15s / s; Opacity range: 3%-8% (to ensure signal stability and avoid overload). (3) Sample loading and testing Sample loading procedure: Quickly transfer the sample cell containing the sample to the instrument inlet inside the glove box. The exposure time should be ≤30 seconds to avoid moisture absorption. Start test: Click "Start" to begin the test. The software will automatically complete feeding, dispersion, optical path scanning, and data acquisition. Data saving: After the test is completed, export the particle size distribution data, including D10, D50, D90, Span, and volume distribution curves, saving them in raw or TXT format.
[0122] Combined with Table 1 and Figures 2-6 Therefore, we can conclude that: Example 1: EDA-ET solvent (10:2), reaction at 60℃ for 6 h, followed by heat treatment at 500℃ for 4 h. The particle size distribution was uniform (D50 = 1.271 μm). Figure 5 As shown; EDS mapping shows that the W elements are uniformly distributed, as... Figure 3 As shown.
[0123] Example 2: EDA-ET solvent (10:1), reaction at 60℃ for 6 h, followed by heat treatment at 450℃ for 3 h. Figure 4 As shown, XRD indicates that the product is free of impurities, confirming that W has successfully entered the crystal lattice.
[0124] Example 3: EDA-EDT solvent (10:1), reaction at 70℃ for 12 h, heat treatment at 520℃ for 5 h, the carbon residue in the EDT system was slightly high (0.8 wt%), but it could be controlled below 1 wt% by high temperature heat treatment.
[0125] Comparative Example 1 used the same raw material ratio as Example 1, and was ball-milled in a ZrO2 ball mill at 600 rpm for 40 hours, followed by heat treatment at 500°C for 4 hours. XRD showed trace amounts of WS2 impurity peaks; Figure 6 As shown, the particle size distribution is uneven, with obvious agglomeration (D50 = 13.565 μm); electrical conductivity (6.5 × 10⁻⁶ μm). -3 S cm -1 (Below the level of the liquid phase method in Example 1)
[0126] Comparative Example 2 used pure ACN instead of EDA-ET, with other conditions the same as in Example 1. WS2 was almost insoluble, and the system was in a black suspension. XRD showed obvious residual WS2 peaks, and EDS mapping showed that the W element distribution was extremely uneven and dissolved. Figure 3 As shown, the conductivity is nearly two orders of magnitude lower than that of Example 1.
[0127] Comparative Example 3 had the same liquid-phase reaction conditions as Example 2, but the heat treatment temperature was mistakenly set to 550°C (it should be 450°C); Figure 4 As shown, excessively high temperatures cause partial decomposition of Sb₂S₃, generating Na₂S impurity phases and sulfur vacancies, resulting in decreased crystal phase purity and a significant drop in electrical conductivity to 9.3 × 10⁻⁶. -4 S cm -1 .
[0128] The electrolyte particles prepared in Examples 1-3 had an average particle size of 1-2 μm and D50 values of 1.271 μm, 1.651 μm, and 2.014 μm, respectively, which were significantly smaller than those prepared by ball milling (Comparative Example 1, D50 = 13.565 μm). Smaller particle size is beneficial for reducing grain boundary impedance and increasing the contact area between the active material and the electrolyte in the composite electrode. Although ball milling can further reduce the particle size through additional wet ball milling, it negatively impacts ionic conductivity. The electrolytes prepared in Examples 1-3 all achieved a room temperature ionic conductivity of 10. -3 S cm -1 The level, of which Example 1 reaches 8.7 × 10 -3 S cm -1 Superior to the ball milling method (6.5×10).-3 S cm -1 This is thanks to the liquid-phase method, which achieves atomically uniform doping of W, resulting in a more ordered distribution of sodium vacancies and lower grain boundary impedance. In contrast, Comparative Example 2, due to the ineffective doping of W, exhibits a conductivity as low as 1.2 × 10⁻⁶. -4 S cm -1 Comparative Example 3 showed that improper heat treatment temperature led to the formation of impurity phases, resulting in a conductivity loss of nearly an order of magnitude.
[0129] A small amount of carbon residue (0.5-0.8 wt%) exists in the liquid-phase product, mainly due to incomplete solvent removal and pyrolysis. The EDT system (Example 3) has slightly higher carbon residue than the ET system (Examples 1-2), but both are controlled below 1 wt%, with limited impact on ionic conductivity. The ball milling method (Comparative Example 1) produces no carbon residue.
[0130] In summary, this invention provides a high-valent cation-doped sulfide solid electrolyte and its liquid-phase synthesis method and application. The liquid-phase synthesis method of the high-valent cation-doped sulfide solid electrolyte includes the following steps: according to the chemical formula Na... 3+δ M 1- x A x S4 is prepared by weighing Na2S, a sulfide containing element M, and elemental A or a sulfide containing element A in stoichiometric proportions. After mixing and grinding, a premixed powder is obtained; wherein M is a Group IV element and / or a Group V element; and A is a +5 or +6 valence metal element. The premixed powder is then mixed with a mixed solvent of organic amine and thiol, and synthesized in the liquid phase to obtain a mixed solution. The solvent is removed from the mixed solution to obtain a precursor powder. The precursor powder is then heat-treated to obtain a tungsten-doped sulfide solid electrolyte. This invention uses a mixed solvent of organic amine and thiol as a high-valence cation to dope Na. 3+δ The MS4 liquid-phase synthesis solvent system utilizes organic amines to induce the deprotonation of thiols, generating nucleophilic thiolate anions. These thiolate anions, with their high nucleophilicity, attack the MS and AS bonds in metal sulfides, causing the original bonds to break and dissociate into soluble complexes. The protonated amine cations act as counterions, stabilizing the soluble complexes. In this mixed solvent, cross-coordination reactions occur between the polyanions generated from the dissociation of different metal sulfides, forming more complex heteropolythiometallic anions, further enhancing the synergistic effect of the solubility of each component. After solvent removal and heat treatment, a high-valence cation-doped sulfide solid electrolyte is obtained. This method is energy-efficient, simple, produces high-purity products, exhibits good uniformity of high-valence cation doping, and leaves no sulfide residue. The resulting electrolyte achieves a sodium ion conductivity of up to 10 at room temperature. -3 S cm -1 This level is suitable for large-scale production.
[0131] It should be understood that the application of the present invention is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.
Claims
1. A liquid-phase synthesis method for a high-valence cation-doped sulfide solid electrolyte, characterized in that, Including the following steps: According to the chemical formula Na 3+δ M 1-x A x S4 is prepared by weighing Na2S, a sulfide containing element M, and elemental A or a sulfide containing element A, mixing and grinding them to obtain a premixed powder; wherein M is a group IV element and / or a group V element; and A is a metal element with a +5 or +6 valence. The premixed powder is mixed with a mixed solvent of organic amine and thiol, and then synthesized in the liquid phase to obtain a mixed solution; The solvent is removed from the mixed solution to obtain the precursor powder; The precursor powder was heat-treated to obtain a high-valence cation-doped sulfide solid electrolyte. Wherein, M is selected from one or more of P, Sb, Sn, and Ge; A is selected from one or more of W, Mo, Ta, Nb, and V; the organic amine is selected from one or more of ethylenediamine and 1,2-propanediamine; the thiol is selected from one or more of ethanethiol, ethylenedithiol, 1,2-propanedithiol, 1,3-propanedithiol, propanethiol, butanethiol, and thiophenol; the volume ratio of the organic amine to the thiol is 10:1 to 10:2; and the concentration of the mixed solution is 30 mg / ml to 60 mg / ml. The liquid phase synthesis temperature is 50℃-70℃, and the liquid phase synthesis time is 4h-12h; The heat treatment temperature is 350℃-550℃, and the heat treatment time is 1h-8h.